The outcomes of secure care in Scotland - Andrew Kendrick; Moira Walker; Aileen Barclay; Lynne Hunter; Margaret Malloch; Malcolm Hill; Gillian McIvor (Scottish Journal of Residential Child Care, 2008)
This paper describes the findings of a three year study (November 2002 – 2005) aimed at developing an understanding of the use and effectiveness of secure accommodation in Scotland (Walker et al. 2006).